2019
DOI: 10.1155/2019/5964127
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Refractive Prediction Error Measured by Optical and Acoustic Biometry after Phacovitrectomy for Rhegmatogenous Retinal Detachment without Macular Involvement

Abstract: Introduction. The aim of this study was to investigate the postoperative prediction error measured by optical biometry and acoustic biometry in eyes after phacovitrectomy for rhegmatogenous retinal detachment (RRD) with no macular involvement. Methods. Forty-nine eyes of 49 patients (32 male, 17 female; mean age 62.6 ± 7.5 years) with RRD without macular involvement who underwent phacovitrectomy (RRD group) and 49 eyes of 33 patients (21 male, 12 female; mean age 74.1 ± 7.1 years) without macular disease who u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
7
1
Order By: Relevance
“…It has been reported that a combined approach may lead to a slight myopic shift when the optical biometry is reliable. A comparable slight postoperative myopic shift has been reported in cases that underwent phacovitrectomy based on fellow-eye biometry 9 , 10 . That point was taken in consideration in the choice of the refraction power of the IOL of our patients, incorporating our own previous experience regarding refractive outcomes after phacovitrectomy.…”
Section: Discussionsupporting
confidence: 69%
“…It has been reported that a combined approach may lead to a slight myopic shift when the optical biometry is reliable. A comparable slight postoperative myopic shift has been reported in cases that underwent phacovitrectomy based on fellow-eye biometry 9 , 10 . That point was taken in consideration in the choice of the refraction power of the IOL of our patients, incorporating our own previous experience regarding refractive outcomes after phacovitrectomy.…”
Section: Discussionsupporting
confidence: 69%
“…Sakamoto et al compared 49 patients undergoing phacovitrectomy for macula-on retinal detachment to 49 patients undergoing cataract surgery alone. They noted a myopic shift in these eyes which required the use of intraocular gas [8]. Although these smaller studies suggested a relationship between intraocular gas and induced myopia after combined cataract surgery and vitrectomy, our results demonstrate that gas tamponade is not a significant factor in refractive error outcomes.…”
Section: Discussion/conclusioncontrasting
confidence: 62%
“…Phacovitrectomy is a safe and effective procedure to treat RRD. Kang et al and Sakamoto et al confirmed that there is a tolerable biometric error after the treatment of RRD with phacovitrectomy in macula-sparing cases, with comparable results obtained with acoustic and optic biometry [ 21 , 22 ]. Although the anatomical and functional results were comparable with those obtained with single PPV and delayed cataract surgery, the refractive outcomes were less favourable and shifted towards myopia, especially in macula-off cases [ 23 ].…”
Section: Discussionmentioning
confidence: 94%